The attack on the protected legal interest: a criminalisation principle and an element of the criminal offence? (Ius Novum, 2023)
This paper analyses the role played by the notion of legal interest as a criterion for decisions on criminalisation and, according to some scholars, as an element of criminal offence. First, the analysis tallies the impact of legal interest on criminal policy, focusing on the correlation between this concept’s definition and underlying political theories. Subsequently, the article explores difficulties of using legal interest as an interpretative canon to determine whether the offender’s deed can be deemed materially unlawful.